The study of food through the analysis of film texts - Febrer Fernández, Nieves (Historia y Comunicación Social, 2014)
The aim of this article is to present a research project based on the exploration of a number of specific parameters focused on the study of food and its social, political, technological, economic and artistic. Our main theme is structured in understanding human habits related to food made through the analysis of film texts. The film illustrates with the full extent of narrative: scientific knowledge and social reality. We entered below in the selection of films that serve as documentary support in the search for sociocultural food fact.